2015
DOI: 10.1017/s1751731115000269
|View full text |Cite
|
Sign up to set email alerts
|

Animal and management factors influencing grower and finisher pig performance and efficiency in European systems: a meta-analysis

Abstract: A meta-analysis on the effects of management and animal-based factors on the performance and feed efficiency of growing pigs can provide information on single factor and interaction effects absent in individual studies. This study analysed the effects of such factors on average daily gain (ADG), feed intake (FI) and feed conversion ratio (FCR) of grower and finisher pigs. The multivariate models identified significant effects of: (1) bedding ( P < 0.01), stage of growth ( P < 0.001) and the interaction bedding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 77 publications
1
20
0
3
Order By: Relevance
“…The efficient usage of resources is a major concern in agri-food production. It has been shown that feed efficiency (FE) of pigs is largely influenced by husbandry environment including dietary composition and dietary energy concentration [ 1 , 2 ]. Moreover, animal-intrinsic factors play an important role in improvement of FE.…”
Section: Introductionmentioning
confidence: 99%
“…The efficient usage of resources is a major concern in agri-food production. It has been shown that feed efficiency (FE) of pigs is largely influenced by husbandry environment including dietary composition and dietary energy concentration [ 1 , 2 ]. Moreover, animal-intrinsic factors play an important role in improvement of FE.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most research regarding the impact of the gastrointestinal tract ( GIT ) on variation in RFI has been conducted under controlled conditions in one environment [24,13], whereby differences in environment, pig age, diet type and selection strategies for RFI used in the different studies may explain the controversial findings [15]. Therefore, we hypothesized that if the size, structure and functionality of the GIT play a role in variation of the RFI in pigs, similar RFI-relationships should be found in low and high RFI pigs which were raised under similar conditions in several environments.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the effects of the interaction between various factors that may influence feed efficiency in pigs (DOUGLAS et al, 2015). According to Heck (2009), it is important to have the domain and to act assertively in the main factors that influence the development of pigs in the growing and finishing phases for these steps to achieve high production costs ( VAN HEUGTEN, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This procedure could improve animal performance, the cost of production and provide an efficient utilization of feed according to each specific situation (TEDESCHI et al, 2005). This resource allows a joint assessment of the effects of one or more factors of production on a particular livestock parameter (VILLALBA MATA, 2000), which provides knowledge about the operation as a whole (GIBON et al, 1999), in contrast to experimental studies in which only a small number of factors are considered, which contributes to limitations in knowing what factors affect the efficiency in the systems of GF pigs (DOUGLAS et al, 2015). However, the use of mathematical models can support decisions regarding demand in production systems with limited information (data used in the model), which is a normal scenario on a farm (TEDESCHI et al, 2005).…”
Section: Introductionmentioning
confidence: 99%